Health Literacy dan Gejala Depresi pada Lansia di Denpasar - Kusuma, Made Dian Shanti; Darmawati, I Dewa Ayu Agra (LPPM Hang Tuah Pekanbaru, 2025)
Health literacy is the ability to seek information, understand, and obtain information about health. It is very important for the older adults to have health literacy, because this ability can help the older adults obtain information about health. If the older adults have good health literacy, then they are able to achieve their physical and psychological well-being.. Objective: to explore the relationship between health literacy and depressive symptoms among older adults in community. Methods: The research design used analytics correlational with a cross-sectional approach. Purposive sampling technique was used in this study with a total sample of 98 older adults. This study was conducted on August 2023 by administering the Health Literacy Short Form Survey Questionnaire) to measure health literacy and the Geriatric Depression Scale to measure depressive symptoms. Data analysis in this study used Spearman Rank analysis. Results: The results of the Spearmen's rank correlation test were r = -0.469 with a significance value of p <0.001. This can be interpreted as meaning that there is a significant relationship between health literacy and depressive symptoms in the elderly. An elderly person who has poor health literacy may be at risk of developing symptoms of depression, and vice versa. Conclusion: Health Literacy is an important indicator that a person must have to achieve the desired health. Health Literacy contributes to reducing risk factors for health problems, both physical and mental.